Thyroid Cancer Advances in Diagnosis and Therapy - Ahmadzadehfar, Hojjat (IntechOpen, 2016)
Thyroid cancer is the eighth most common type of cancer and is most frequently diagnosed among people aged 45-54. Nearly three out of four cases are found in women, while about 2% of thyroid cancers occur in children and teenagers. This book is for medical doctors with experience in the field of thyroid cancer. It comprises different subjects, especially the advances in the diagnosis of thyroid cancer with PET imaging and elastography, as well as the new therapeutic approaches with tyrosine kinase inhibitors.